2014
DOI: 10.1002/qj.2489
|View full text |Cite
|
Sign up to set email alerts
|

Foehn warming distributions in nonlinear and linear flow regimes: a focus on the Antarctic Peninsula

Abstract: The structure of lee-side warming during foehn events is investigated as a function of cross-barrier flow regime linearity. Two contrasting cases of westerly flow over the Antarctic Peninsula (AP) are considered – one highly nonlinear, the other relatively linear. Westerly flow impinging on the AP provides one of the best natural laboratories in the world for the study of foehn, owing to its maritime setting and the Larsen C Ice Shelf (LCIS) providing an expansive, homogeneous and smooth surface on its east si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
108
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 51 publications
14
108
1
Order By: Relevance
“…Local föhn events were identified based on three criteria, namely wind direction, wind speed and duration. Previous studies revealed that föhn at Larsen C ice shelf is governed by upwind conditions at higher altitude [22,23]. Manual checking of wind direction at 500 hPa showed a positive föhn identification error of only 1.2%, likely caused by the stringent minimum wind speed criterion of 4 m s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Local föhn events were identified based on three criteria, namely wind direction, wind speed and duration. Previous studies revealed that föhn at Larsen C ice shelf is governed by upwind conditions at higher altitude [22,23]. Manual checking of wind direction at 500 hPa showed a positive föhn identification error of only 1.2%, likely caused by the stringent minimum wind speed criterion of 4 m s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic of the upwind flow, as described by ĥ, can have important consequences for the strength, frequency, and spatial characteristics of foehn warming over the eastern side of the peninsula. Linear flows have been shown associated with more extensive warming along the northeastern AP, with weaker temperature signatures and more topographic channeling of flow observed for nonlinear flows [ Elvidge et al , ]. While only the single record at Matienzo is available prior to 2010, characterizing the nature of the flow over the peninsula with the more recent records as well as upwind flow characteristics gives insight into the expected spatial variability in foehn winds over the long term.…”
Section: Methodsmentioning
confidence: 99%
“…During these two periods, flights were made to study a variety of meteorological phenomena, including boundary layer (Fiedler et al, 2010), orographic flow (Elvidge et al, 2014), and cloud studies. A total of 64 flights were completed during these periods.…”
Section: Aircraft Measurementsmentioning
confidence: 99%